The effect of coenzyme Q10 on cognitive status in chronic hemodialysis patients; a double-blind, randomized, clinical trial - Mohammad Reza Tamadon; Majid Mirmohammadkhani; Shahb Rafaati (Society of Diabetic Nephropathy Prevention, 2018)
Introduction: Renal failure is a stressful process that has several complications, including neurological disorders such as cognitive disorder, which can lead to the incidence of psychological disorders. Objectives: Given the reduced coenzyme Q10 levels in patients with chronic renal failure and the known role of this coenzyme in cognitive disorders, the present study was conducted to assess the effect of CoQ10 supplementation in the treatment of cognitive disorder in hemodialysis patients in Semnan, Iran. Patients and Methods: The present double-blind, randomized, clinical trial was conducted on patients with chronic renal failure undergoing hemodialysis at Kosar Hospital of Semnan. The participants underwent a cognitive assessment using the Mini-Mental State Examination (MMSE). They were then randomly divided into two groups; group one received CoQ10 supplement and group two received placebo for 90 days, after which period they underwent another cognitive assessment using the MMSE. The Kolmogorov-Smirnov test and Levene's test were used to verify the normal distribution of the data. Data were analyzed using the t test and Mann-Whitney U test at a significance level of P<0.05. Results: There were no statistically significant differences between the two groups in terms of their personal details. The mean (± standard deviation) of the MMSE1 score was 21.29±6.5 in the control group and 21.09±5.4 in the case group. The mean (± standard deviation) of the MMSE2 score was 20.62±6.5 in the control group and 23.29±5.8 in the case group. A significant difference between the two groups in terms of their pre- and post-intervention MMSE scores was observed, suggesting the positive effect of the medication (P<0.001). Conclusion: The daily intake of CoQ10 100-mg led to a significant change in the cognitive status of chronic hemodialysis patients compared to the group that received only the placebo. Conducting a similar study but with the addition of a healthy control group is recommended in order to establish a base measure for the healthy population and to thus enable the better interpretation of the effect of this supplement.